Biocontrol of strawberry gray mold caused by Botrytis cinerea with the termite associated Streptomyces sp. sdu1201 and actinomycin D - Yong, Daojing; Li, Yue; Gong, Kai; Yu, Yingying; Zhao, Shuai; Duan, Qiong; Ren, Cailing; Li, Aiying; Fu, Jun; Ni, Jinfeng; Zhang, Youming; Li, Ruijuan (Frontiers in Microbiology, 2022)
Strawberry gray mold disease caused by Botrytis cinerea is one of the most severe diseases in pre- and post-harvest periods. Although fungicides have been an effective way to control this disease, they can cause serious "3R" problems (Resistance, Resurgence and Residue). In this study, Streptomyces sp. sdu1201 isolated from the hindgut of the fungus-growing termite Odontotermes formosanus revealed significant antifungal activity against B. cinerea. Four compounds (1−4) were isolated from Streptomyces sp. sdu1201 and further identified as actinomycins by the HRMS and 1D NMR data. Among them, actinomycin D had the strongest inhibitory activity against B. cinerea with the EC50 value of 7.65 μg mL-1. The control effect of actinomycin D on strawberry gray mold was also tested on fruits and leaves in vitro, and its control efficiency on leaves was 78.77% at 3 d. Moreover, actinomycin D can also inhibit the polarized growth of germ tubes of B. cinerea. Therefore, Streptomyces sp. sdu1201 and actinomycin D have great potential to gray mold as biocontrol agents.